Contribution of Teacher Readliness and Learning Facilities to the Implementation of the Independent Curriculum at SMK Negeri 5 Padang - Putri Ardini; Efrizon Efrizon; Ilmiyati Rahmy Jasril; Dedy Irfan (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2025)
Teachers' preparedness and sufficient learning resources are necessary for vocational schools to adopt the Independent Curriculum (Kurikulum Merdeka). This study aims to investigate the effects of learning resources and teacher preparation on SMK Negeri 5 Padang`s implementation of the Independent Curriculum. 18 teachers from the departments of electrical installation and electronics were given questionnaires to complete in order to gather data for the study, which uses a quantitative correlational approach. According to the results, learning facilities account for 23% of the implementation of the Independent Curriculum, while teacher preparedness accounts for 37.2%. Additionally, the combined effect of these two elements is 46.4%, indicating that the availability of learning facilities and teacher preparedness are both essential for the successful implementation of the curriculum. According to the study, in order to maximize the effectiveness of the Independent Curriculum, schools should improve learning infrastructure and teacher training.